2019
DOI: 10.1051/e3sconf/201911101042
|View full text |Cite
|
Sign up to set email alerts
|

Relation between energy use and indoor thermal environment in animal husbandry: a case study

Abstract: Climate control is of the foremost importance in structures for intensive animal rearing because many animals (e.g. pigs and broilers) tolerate a small range of climate conditions (mainly air temperature and relative humidity) that may differ considerably from the outdoor environment. For this reason, the indoor climate in the majority of structures for animal husbandry is guaranteed by HVAC systems. On the one hand, the use of mechanical systems makes it possible to avoid production risks due to the unpredict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…When calculating the overall energy loss, it was found to be 11.78% and 8.13% due to pigs' different activities (physical activity, fasting heat production, and wastewater) and proper airflow management of the barn, respectively. This percentage is lower than the value reported by Kil [32] and Bilardo et al [43]. Kil [32] reported that 15.40% of energy was lost by pigs' different activities, while Bilardo et al [43] measured that around 17% of total energy was used to manage the barn airflow.…”
Section: Energy Balance Of the Experimental Pig Barnmentioning
confidence: 64%
See 1 more Smart Citation
“…When calculating the overall energy loss, it was found to be 11.78% and 8.13% due to pigs' different activities (physical activity, fasting heat production, and wastewater) and proper airflow management of the barn, respectively. This percentage is lower than the value reported by Kil [32] and Bilardo et al [43]. Kil [32] reported that 15.40% of energy was lost by pigs' different activities, while Bilardo et al [43] measured that around 17% of total energy was used to manage the barn airflow.…”
Section: Energy Balance Of the Experimental Pig Barnmentioning
confidence: 64%
“…This percentage is lower than the value reported by Kil [32] and Bilardo et al [43]. Kil [32] reported that 15.40% of energy was lost by pigs' different activities, while Bilardo et al [43] measured that around 17% of total energy was used to manage the barn airflow. The remaining 10.89% of energy was used to manage the barn temperature and illuminate the barn.…”
Section: Energy Balance Of the Experimental Pig Barnmentioning
confidence: 64%
“…As part of the EPAnHaus (Energy Performance of Animal House) project (2014-2017), a study was conducted to assess the relationship between animal welfare, indoor climate conditions, and energy use for two buildings housing GFP in North West Italy (Bilardo et al 2019). The structures of the buildings were comparable, with fully slatted concrete floors, sandwich roofs (likely metal sheets and insulation), and hollow concrete wall blocks.…”
Section: Resultsmentioning
confidence: 99%
“…The first one was by , as it was clearly related to and complemented the article by Peters et al (2015) on relevant IAQ issues. The second was a review of used energy and thermal climate models in Europe as part of the EPAnHaus project (Bilardo et al 2019). All references were summarised using one mind map per reference, which included the research aim, method, important results, and main conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…Pig productivity can also be affected by heat stress. According to the experimental results of Bilardo et al [46], growing-finishing pigs tend to not feed when indoor air temperatures are excessively high. Furthermore, growth performance and intestinal function of pigs can be affected by the increased gut permeability and inflammation caused by heat stress [43].…”
Section: Climate Control and Productivitymentioning
confidence: 99%